Prolonged Detection of Zika Virus RNA in Pregnant Women. Issue 4 (October 2016) - Meaney-Delman, Dana; Oduyebo, Titilope; Polen, Kara N.D.; White, Jennifer L.; Bingham, Andrea M.; Slavinski, Sally A.; Heberlein-Larson, Lea; St. George, Kirsten; Rakeman, Jennifer L.; Hills, Susan; Olson, Christine K.; Adamski, Alys; et al.
Abstract : OBJECTIVE: Zika virus infection during pregnancy is a cause of microcephaly and other fetal brain abnormalities. Reports indicate that the duration of detectable viral RNA in serum after symptom onset is brief. In a recent case report involving a severely affected fetus, Zika virus RNA was detected in maternal serum 10 weeks after symptom onset, longer than the duration of RNA detection in serum previously reported. This report summarizes the clinical and laboratory characteristics of pregnant women with prolonged detection of Zika virus RNA in serum that were reported to the U.S. Zika Pregnancy Registry. METHODS: Data were obtained from the U.S. Zika Pregnancy Registry, an enhanced surveillance system of pregnant women with laboratory evidence of confirmed or possible Zika virus infection. For this case series, we defined prolonged detection of Zika virus RNA as Zika virus RNA detection in serum by real-time reverse transcription-polymerase chain reaction (RT-PCR) 14 or more days after symptom onset or, for women not reporting signs or symptoms consistent with Zika virus disease (asymptomatic), 21 or more days after last possible exposure to Zika virus. RESULTS: Prolonged Zika virus RNA detection in serum was identified in four symptomatic pregnant women up to 46 days after symptom onset and in one asymptomatic pregnant woman 53 days postexposure. Among the five pregnancies, one pregnancy had evidence of fetal Zika virus infection confirmed by histopathologic examination of fetal tissue, three pregnancies resulted in live births of apparently healthy neonates with no reported abnormalities, and one pregnancy is ongoing. CONCLUSION: Zika virus RNA was detected in the serum of five pregnant women beyond the previously estimated timeframe. Additional real-time RT-PCR testing of pregnant women might provide more data about prolonged detection of Zika virus RNA and the possible diagnostic, epidemiologic, and clinical implications for pregnant women. Abstract : In some pregnant women, Zika virus RNA can be detected for a prolonged period, which might have diagnostic, epidemiologic, and clinical implications.Supplemental Digital Content is Available in the Text.